A new data infrastructure for family research and demographic analysis: the German Family Demography Panel Study (FReDA) - Hank, Karsten; Gummer, Tobias; Bujard, Martin; Neyer, Franz J.; Pollak, Reinhard; Spieß, C. Katharina; Wolf, Christof; Christmann, Pablo; Kunz, Tanja; Lück, Detlev; Naderi, Robert; Nutz, Theresa; et al. (European sociological review, 2025)
This data brief introduces the German Family Demography Panel Study (FReDA; https://www.freda-panel.de/), a longitudinal, multi-actor database for family research. Major substantive fields addressed in the questionnaire include fertility-related attitudes and behaviours, reproductive health, work-family conflict, couples’ division of labour, gender roles, intimate relationships, separation and divorce, parenting and intergenerational relations, and well-being. FReDA is based on two initially independent samples: the newly drawn FReDA-GGS sample (n_recruitment = 37,777 respondents, aged 18-49 years), constituting the German contribution to the Generations and Gender Surveys (GGS-II), and the FReDA-pairfam sample (n = 6,216 respondents who originally participated in the German Family Panel [pairfam]). Both samples are fully integrated, using one survey instrument consisting of the harmonized GGS-II and pairfam questionnaires. Mainly web-based interviews, complemented by paper-based interviews, are conducted biannually, with one wave being split across two subwaves. We provide a short description of FReDA’s forerunners—the GGS and pairfam—and give an overview of FReDA’s design and content, its baseline wave (collected in 2021) and data releases, as well as a brief outlook on FReDA’s road ahead.